Antibacterial and antibiofilm activity of bone marrow-derived human mesenchymal stem cells secretome against Vibrio cholerae. (February 2020) - Bahroudi, Mahboube; Bakhshi, Bita; Soudi, Sara; Najar-peerayeh, Shahin
Abstract: The ability of V. cholerae to survive and spread in the aquatic environment combined with the scarcity of effective antimicrobial agents, especially those effective against multidrug-resistant strains highlights the need for alternative non-antibiotic approaches for the treatment of V. cholerae infections. The aim of this study was to specifically examine the potential direct effect of unstimulated MSC secretome on V. cholerae killing and biofilm formation as a representative of non-invasive enteric bacterial pathogen. The bmMSCs were characterized by the presence of CD44 and CD73 and the absence of CD45 and CD34 molecular markers. Moreover, self-regeneration and differentiation capacity of MSCs into adipocytes and osteogenic lineages was assessed by immunohistology (IHC) method. The antibacterial activity of unstimulated MSCs supernatant against V. cholerae in broth microdilution assay decreased the bacterial suspension from 10 8  CFU/ml to 10 7  CFU/ml and showed a significant antimicrobial activity in a dose-dependent manner at dilutions of 1:8 to 1:128 ( P  < 0.05). The role of MSC secretome without preconditioning in the prevention of biofilm formation was assessed through plate-crystal violet assay and showed high antibiofilm activity against V. cholerae also in dose-dependent manner. As antibacterial mechanisms of MSC secretome are different from conventional antibiotics, together with its antibiofilm activity, proposes its application as a novel therapeutic approach combatting multi‐drug resistant pathogens with no fear of developing antimicrobial resistance. Highlights: Unstimulated MSCs secretome showed a significant antimicrobial activity against V. cholerae in a dose-dependent manner. MSC secretome with no preconditioning prevented biofilm formation of V. cholerae also in dose-dependent manner. MSCs secretome can be applied as novel antimicrobial agents with no fear of developing antimicrobial resistance.